2014
DOI: 10.3892/etm.2014.2088
|View full text |Cite
|
Sign up to set email alerts
|

Ulinastatin ameliorates acute kidney injury following liver transplantation in rats and humans

Abstract: Acute kidney injury (AKI) is a common complication following orthotopic liver transplantation (OLT) that evidently affects prognosis. However, no effective treatment exists for AKI. The aim of the present study was to elucidate whether ulinastatin application during OLT in humans can reduce kidney damage and improve renal function. In addition, the underlying mechanisms of ulinastatin were investigated on a rat autologous OLT (AOLT) model. In total, 60 patients undergoing an OLT were randomly selected to recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
(31 reference statements)
1
6
0
Order By: Relevance
“…Recently, Li and colleagues [ 7 ] report that ulinastatin could be an effective treatment for AKI following liver transplantation in rats and humans and their study suggests that ulinastatincan protect against AKI following orthotopic liver transplantation by inhibiting inflammation and oxidation. However, the effectiveness of ulinastatin in the treatment of AKI caused by HLF and its mechanisms are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Li and colleagues [ 7 ] report that ulinastatin could be an effective treatment for AKI following liver transplantation in rats and humans and their study suggests that ulinastatincan protect against AKI following orthotopic liver transplantation by inhibiting inflammation and oxidation. However, the effectiveness of ulinastatin in the treatment of AKI caused by HLF and its mechanisms are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Mice were separated into three groups ( n = 10 mice/group) at random: bilateral ovariectomized mice intraperitoneal injected with ulinastatin (1 × 10 5 units/kg per day) (OVX + ulinastatin), bilateral ovariectomized mice intraperitoneal injected with isopyknic DMSO (OVX), sham-operated mice intraperitoneal injected with isopyknic DMSO (SHAM). The injection dose of ulinstatin refers to previous studies and the dose is similar to therapeutic dose ( Shen et al, 2014 ; Li et al, 2015 ). Ulinstatin solution and DMSO were administered by intraperitoneal injection in the mice seven times a week for 6 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Similar findings were observed in previous studies [5,11,[14][15][16][17] suggesting that hepatic I/R injury damages both the morphology and the function of the kidney [16,18,19]. Moreover, several studies reported pathological alterations in kidneys according to the period of reperfusion ranging from 1 to 24 h. After 1-h kidney showed moderate hemorrhage and congestion [20], eosinophilic appearance and perinuclear vacuolic formation in tubular cells [17] after 8 h showing loss of brush border and tubular epithelium with hyaline casts and congestion [21], while other researches showed tubular dilatation and necrosis, cellular swelling, and granular casts after 24-h reperfusion [5,14,22]. Kadkhodaee et al [23] showed that hepatic and renal dysfunction were seen markedly after 4 h than 24-h reperfusion.…”
Section: Discussionmentioning
confidence: 66%